The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.clinre.2015.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation plus chemoembolization versus radiofrequency ablation alone for hepatocellular carcinoma: A systematic review and meta-analysis

Abstract: TACE combined with RFA was more effective than RFA alone, especially for treatment for intermediate and large-size hepatic tumours or younger patients with HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 27 publications
(41 reference statements)
5
43
0
1
Order By: Relevance
“…Another very recent RCT [42] showed that TACE-RFA was superior to RFA alone in improving survival for patients with HCC <7 cm. Moreover, several independent meta-analyses [43,44,45,46], including the RCTs available for RFA plus TACE compared with RFA alone, confirmed high-quality evidence suggesting that TACE in combination with RFA improved survival outcomes compared with RFA alone for patients with HCC, particularly for tumors >3 cm in size. An alternative strategy using localized radiation in combination with RFA has also been studied [47].…”
Section: Local Ablative Therapymentioning
confidence: 79%
“…Another very recent RCT [42] showed that TACE-RFA was superior to RFA alone in improving survival for patients with HCC <7 cm. Moreover, several independent meta-analyses [43,44,45,46], including the RCTs available for RFA plus TACE compared with RFA alone, confirmed high-quality evidence suggesting that TACE in combination with RFA improved survival outcomes compared with RFA alone for patients with HCC, particularly for tumors >3 cm in size. An alternative strategy using localized radiation in combination with RFA has also been studied [47].…”
Section: Local Ablative Therapymentioning
confidence: 79%
“…Complications associated with TACE, including an impaired hepatic functional reserve, support the use of RFA rather than repeated TACE treatments (22,23). Emerging evidence suggests that a combination of TACE and RFA exerts a synergistic anticancer activity against HCC, particularly for larger lesions that do not respond sufficiently to either TACE or RFA treatments alone (24)(25)(26). An analysis of the factors that carry a high risk of early recurrence following TACE may improve the selection of patients suited to a combination of TACE with RFA.…”
Section: Discussionmentioning
confidence: 99%
“…Through the protection of liver function and regulation of body immunity, TCM can also improve the patient's quality of life (QOL) and reduce adverse reactions [25,26]. In some cases, if long-term using TCM treatment, HCC could be completely regressed and the patient remains alive longer than 31 months after relapse [27]. Additionally, hepatic fibrosis, cirrhosis and rate of HCC occurrence in patients have been significantly inhibited [28,29].…”
Section: Treatment Of Hcc Using Tcm Alone or In Combination With Othementioning
confidence: 99%
“…The results showed that with both, TCM had a positive effect in the treatment of HCC. Although direct use of TCM by hepatic artery perfusion/embolization has a good effect [96,97], multimodal treatment strategy, such as RFA + TACE [98], radiofrequency ablation + TACE + hepatectomy [99], TCM+ WM+ intervention [100], is more effective than that of interventional therapy alone for patients. Additionally, multimodal treatment can be used as a helpful bridging therapy for patients who are waiting for liver transplantation.…”
Section: Combination Of Tcm and Interventional Therapy For Treatment mentioning
confidence: 99%